Adsorption analysis of organic and chemical sorbents for oil spill management on land - Sanjukta Baruah; Dhrubajyoti Neog (Results in Engineering)
This study aims to evaluate the effectiveness of chemical and biodegradable agricultural waste sorbents in remediating oil spill-contaminated well sites in the upper Assam Basin of India. The study involved laboratory analyses to analyze the physical characteristics of oil-spill fluids and evaluate the impact of spillage on soil. Soil samples were tested for pH, organic carbon, potash, sulfur, phosphate, and total nitrogen. Soil characteristics before and after the spills were compared. Of the five soil samples examined, three were treated with two chemical sorbents (sodium lauryl sulfate and sodium dodecylbenzene sulfonate) and one biosorbent was made from agricultural waste (rice husk). Rice husks were chosen because of their abundant availability in the area. The adsorption performance of the chemical sorbents was evaluated using wettability analysis, and the sorbent absorption behavior was investigated using UV–visible spectrophotometry. The findings of this study emphasize the use of organic sorbents to remediate hydrocarbon-contaminated sites, presenting them as cost-effective and environmentally safe alternatives to chemical sorbents. Based on the soil testing results of pre- and post-sorbent treatments with sodium dodecylbenzene sulfonate (SDBS), it was observed that SDBS improved the pH to 9.69 from 6.68; organic matter to 5.33 from 0.74; organic carbon to 3.09 % from 0.43 %; available potash (K₂O ppm) to 83 ppm from 20 ppm; sulfur content to 68 ppm from 50 ppm; available phosphate (P₂O₅) to 27 ppm from 13 ppm; and % nitrogen to 0.262. These values infer higher performance of SDBS sorbent than sodium lauryl sulfate sorbent. In addition, the sorption capacity of organic sorbent (rice husk) increased to 1.255 g/g.